Of Humans and Gerbils— Independent Diversification of Neuroligin-4 Into X- and Y-Specific Genes in Primates and Rodents - Maxeiner, Stephan; Benseler, Fritz; Brose, Nils; Krasteva-Christ, Gabriela (Frontiers in Molecular Neuroscience, 2022)
The neural cell adhesion protein neuroligin-4 has puzzled neuroscientists and geneticist alike for almost two decades. Its clinical association with autism spectrum disorders, ASD, is well established, however, its diversification into sex chromosome-specific copies, NLGN4X and NLGN4Y, remains uncharted territory. Just recently, the presence of substantial neuroligin-4 sequence differences between humans and laboratory mice, in which Nlgn4 is a pseudoautosomal gene, could be explained as a consequence of dramatic changes affecting the pseudoautosomal region on both sex chromosomes in a subset of rodents, the clade eumuroida. In this study, we describe the presence of sex chromosome-specific copies of neuroligin-4 in the Mongolian gerbil (Meriones unguiculatus) marking the first encounter of its kind in rodents. Gerbils are members of the family Muridae and are closely related to mice and rats. Our results have been incorporated into an extended evolutionary analysis covering primates, rodents, lagomorphs, treeshrews and culogos comprising the mammalian superorder euarchontoglires. We gathered evidence that substantial changes in neuroligin-4 genes have also occurred outside eumuroida in other rodent species as well as in lagomorphs. These changes feature, e.g., a general reduction of its gene size, an increase in its average GC-content as well as in the third position (GC3) of synonomous codons, and the accumulation of repetitive sequences in line with previous observations. We further show conclusively that the diversification of neuroligin-4 in sex chromosome-specific copies has happened multiple times independently during mammal evolution proving that Y-chromosomal NLGN4Y genes do not originate from a single common NLGN4Y ancestor.